2003
DOI: 10.1091/mbc.e03-03-0187
|View full text |Cite
|
Sign up to set email alerts
|

Myosin IIA Drives Neurite Retraction

Abstract: Neuritic extension is the resultant of two vectorial processes: outgrowth and retraction. Whereas myosin IIB is required for neurite outgrowth, retraction is driven by a motor whose identity has remained unknown until now. Preformed neurites in mouse Neuro-2A neuroblastoma cells undergo immediate retraction when exposed to isoform-specific antisense oligonucleotides that suppress myosin IIB expression, ruling out myosin IIB as the retraction motor. When cells were preincubated with antisense oligonucleotides t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
83
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 77 publications
(109 reference statements)
6
83
0
Order By: Relevance
“…Although NMII isoforms share somewhat overlapping roles, each isoform has distinctive tissue distribution and specific functions. NMII-A is important for neural growth cone retraction (17,18) and is distributed to the front of migrating endothelial cells (19). While NMII-B participates in growth cone advancement (20) and was detected in the retracting tails of migrating endothelial cells (19).…”
Section: Non Muscle Myosin II (Nmii)mentioning
confidence: 99%
“…Although NMII isoforms share somewhat overlapping roles, each isoform has distinctive tissue distribution and specific functions. NMII-A is important for neural growth cone retraction (17,18) and is distributed to the front of migrating endothelial cells (19). While NMII-B participates in growth cone advancement (20) and was detected in the retracting tails of migrating endothelial cells (19).…”
Section: Non Muscle Myosin II (Nmii)mentioning
confidence: 99%
“…It contributes to retrograde flow and actin filament organization and advance (Bridgman et al., 2001;Medieros et al, 2006). In addition it is important for turning in response to borders of substrate-bound laminin-1 (Turney and Bridgman, 2005) and for neurite retraction including that induced by Sema 3A (Gallo et al, 2002;Wylie and Chantler, 2003;Gallo, 2006), indicating that it may be of general importance for growth cone steering. Several studies have shown axon retraction can be prevented by inhibiting upstream regulators of myosin motors (Ahmad et al, 2000) or by reducing the amount of active myosin II in neuroblastoma cells (Wylie and Chantler, 2003 kinase, a myosin II regulatory protein, can prevent retraction in response to guidance factors (Wahl et al, 2000;Gallo, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, COS-7 cells express little or no myosin IIA (Buxton et al, 2003), suggesting that myosin IIA may be particularly important for the Sema 3A response in neurons. DRG neurons express multiple forms of myosin II, including myosin IIA, which has been shown to be involved in neurite retraction of neuroblastoma cells (Wylie and Chantler, 2003). However, it remains unclear if both collapse and retraction are normally part of the response to Sema 3A and if so, to what degree these different phases of response depend on myosin II isoforms.…”
Section: Introductionmentioning
confidence: 99%
“…Thrombin-induced cell rounding was also blocked following M2A depletion or Y27632 treatment, but not by M2B depletion-a comparable situation to that observed with regard to neurite retraction . These targeted knockdown studies Sandquist et al 2006), as well as Rho-kinase overexpression studies (Amano et al 1998), define separate, yet linked, functions for M2A and M2B and indicate that M2A is downstream of Rho-ROCK signalling, while M2B is downstream of Rac (van Leeuwen et al 1999;Wylie and Chantler 2003;Chantler and Wylie 2003;Sandquist et al 2006). M2C is functionally distinct, complementing the actions of M2B with respect to neurite outgrowth, yet operating alongside M2A with respect to adhesion (Wylie and Chantler 2008); however, its upstream control pathways are not well defined at present.…”
Section: Neurite Outgrowth and Axonal Guidancementioning
confidence: 99%
“…At the leading edge of the growth cone is a broad, relatively thin, veil-like lamellipodium, actin polymerisa-tion pushing the plasma membrane forwards (Pantaloni et al 2001;Pollard and Borisy 2003); actin filaments, thus formed, are translocated rearwards, initiating a phenomenon known as retrograde actin flow. The forces required to move the bulk of the growth cone forwards are much greater than can be achieved through actin polymerisation alone, hence a requirement for myosin 2 molecular motors, which act vectorially and power forward outgrowth (Wylie et al 1998;Bridgman et al 2001) and rearward retraction (Amano et al 1998;Wylie and Chantler 2003), as well as retrograde actin flow (Lin et al 1996;Cai et al 2006;Medeiros et al 2006). Similar actions underpin the generation of protrusions in non-neuronal cells.…”
Section: Neurite Outgrowth and Axonal Guidancementioning
confidence: 99%